PENGARUH MODAL KERJA, STRUKTUR MODAL, DAN LIKUIDITAS TERHADAP HARGA SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI TAHUN 2022-2024 - Nazilatul Rizqiyana; Ika Wahyuni; Triska Dewi Pramitasari (Fakultas Ekonomi dan Bisnis, 2026)
This study was conducted to analyze the influence of working capital, capital structure, and liquidity on stock prices, with profitability as an intervening variable. Mining companies listed on the Indonesia Stock Exchange in 2022-2024 were the subjects of this study.The analytical method used was Partial Least Squares (PLS) using the Smart PLS 3.0 application, which includes classical assumption tests, including multicollinearity and normality tests, coefficient of determination tests, structural equation analysis (Inner Model), and research hypothesis testing. The results of the study indicate that working capital and capital structure have a positive but insignificant effect on profitability, while liquidity has a negative but insignificant effect on profitability. Furthermore, working capital, capital structure, and liquidity each have a positive but insignificant effect on stock prices. Profitability also shows a negative but insignificant effect on stock prices. The results of the indirect effect hypothesis test indicate that working capital and capital structure have a negative but insignificant effect on stock prices through profitability. Meanwhile, liquidity has a positive but insignificant effect on stock prices through profitability.